Rational Design of Pt−Pd−Ni Trimetallic Nanocatalysts for Room‐Temperature Benzaldehyde and Styrene Hydrogenation. Issue 16 (30th June 2021) - Zheng, Tuo; Wu, Fengshun; Fu, Huan; Zeng, Li; Shang, Congxiao; Zhu, Lihua; Guo, Zhengxiao
Abstract: Nanostructures of the multimetallic catalysts offer great scope for fine tuning of heterogeneous catalysis, but clear understanding of the surface chemistry and structures is important to enhance their selectivity and efficiency. Focussing on a typical Pt−Pd−Ni trimetallic system, we comparatively examined the Ni/C, Pt/Ni/C, Pd/Ni/C and Pt−Pd/Ni/C catalysts synthesized by impregnation and galvanic replacement reaction. To clarify surface chemical/structural effect, the Pt−Pd/Ni/C catalyst was thermally treated at X=200, 400 or 600 °C in a H2 reducing atmosphere, respectively termed as Pt−Pd/Ni/C−X. The as‐prepared catalysts were characterized complementarily by XRD, XPS, TEM, HRTEM, HS‐LEIS and STEM‐EDS elemental mapping and line‐scanning. All the catalysts were comparatively evaluated for benzaldehyde and styrene hydrogenation. It is shown that the "PtPd alloy nanoclusters on Ni nanoparticles" (PtPd/Ni) and the synergistic effect of the trimetallic Pt−Pd−Ni, lead to much improved catalytic performance, compared with the mono‐ or bi‐ metallic counterparts. However, with the increase of the treatment temperature of the Pt−Pd/Ni/C, the catalytic performance was gradually degraded, which was likely due to that the favourable nanostructure of fine "PtPd/Ni" was gradually transformed to relatively large "PtPdNi alloy on Ni" (PtPdNi/Ni) particles, thus decreasing the number of noble metal (Pt and Pd) active sites on the surface of the catalyst. The optimum trimetallic structure is thus the as synthesised Pt−Pd/Ni/C. This work provides a novel strategy for the design and development of highly efficient and low‐cost multimetallic catalysts, e. g. for hydrogenation reactions. Abstract : Pt−Pd−Ni trimetallic catalysts were successfully designed, synthesized and/or further heat‐treated. The as‐synthesized Pt−Pd/Ni/C catalyst consists of PtPd alloy nanoclusters on Ni nanoparticles, whereas it showed a structure of PtPdNi alloy clusters on Ni nanoparticles (Pt−Pd/Ni/C‐600) after further treatment in H2 . The former exhibited superior catalytic performance for benzaldehyde (styrene) hydrogenation at room temperature